Editorial Note - David Barker; Michael Adams (Legal Education Review)
Law schools are in the business of training “lawyers”, that is, people who will practise law. Law schools are not in the business of training students to only be able to regurgitate what they have learned in a bar exam. Lawyers must interact with a plethora of different people. They include clients, colleagues, opposing counsel, judges, witnesses, probation officers, court staff, support staff and others. Clients are often in crisis and, thus, emotional. Law schools must train students to effectively and intelligently interact with people on an emotional basis if we are to train students to be effective, good lawyers. This paper will briefly give an overview of what is meant by “emotional intelligence” and why it is important to the law school curriculum. The primary focus of the paper will be relating my experience in offering a class on emotional intelligence in the internship program at the University of Denver College of Law, Colorado, USA. I will discuss the goals and objectives that I had; the preconceptions that I brought into the process; the organisation of the class; the methodology utilised; the materials used; the student’s reactions; and, finally, what modifications I would make to the course.